SISTEM WARISAN BUDAYA TAKBENDA – TANTANGAN PELESTARIAN BUDAYA DALAM PERSPEKTIF LINTAS BUDAYA - Marzanna Poplawska (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2025)
This article examines over a decade of research and observations on the development of policies related to Intangible Cultural Heritage (ICH) and their impact on terminology, administrative structures, and types of protective measures. The primary data collection, including extensive fieldwork, took place between 2022 and 2024. I explore the influence of the UNESCO Convention for the Safeguarding of the Intangible Cultural Heritage (2003) on performing arts and local communities in Indonesia and Poland. The two countries provide distinct examples of different societal contexts: one European and relatively homogeneous, the other postcolonial and highly diverse. The article presents findings from my research on selected performing arts inscribed on the UNESCO list: Indonesia’s angklung and pencak silat, and Poland’s polonaise. Through the analysis of these examples, framed within a broader cultural context, I demonstrate how the ICH system affects, or fails to affect, the status of traditional performing arts, the interpretations of cultural heritage, and the evolving roles of culture.